Use of Hibiscus rosa-sinensis as a Green Corrosion Inhibitor for Valve Materials in RO Water - Pudjiwati, Sri; Sanusi, Yasa; Arwati, I Gusti Ayu (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2025)
Valves are mechanical devices that regulate the flow of oil and gas fluids and are typically constructed from materials that are heat-resistant, corrosion-resistant, and capable of withstanding high pressure. However, observations from valve manufacturing companies in the Banten area have shown that valve components made from medium carbon steel ASTM A105N are susceptible to corrosion during hydrotesting, particularly when using reverse osmosis (RO) water as the testing medium. This corrosion can degrade product quality before delivery to customers. To address this issue, this study investigates the use of Hibiscus rosa-sinensis as a green corrosion inhibitor. The objective of this research is to evaluate the corrosion rate, inhibitor efficiency, and surface morphology of ASTM A105N valve materials using Hibiscus rosa-sinensis in RO water media, with varying inhibitor concentrations and immersion durations. The electrochemical methods used include Potentiodynamic Polarization, Electrochemical Impedance Spectroscopy (EIS), Chronoamperometry, and Scanning Electron Microscopy (SEM). Results from the corrosion rate tests indicated that the highest inhibitor efficiency—59.04%—was achieved at 24 hours of immersion with a 2 g inhibitor concentration. This condition also yielded the lowest corrosion rate of 1.2231 × 10⁻² mm/year and the lowest corrosion current (Icorr) of 3.2601 × 10⁻⁶ A/cm². Chronoamperometry testing confirmed these findings with the lowest electric charge value of 0.0125 C. SEM analysis further revealed a more uniform and homogeneous protective coating on the metal surface under these conditions. Based on these results, Hibiscus rosa-sinensis demonstrates promising performance as a green corrosion inhibitor and is recommended as an additive in RO water for valve hydrotesting. This study highlights the potential of environmentally friendly and cost-effective inhibitors in reducing corrosion risk in valve materials.